Testicular Tuberculosis with Tuberculoma of Brain in an HIV Negative Patient - Khanom, Mehrunnissa (Journal of Bangladesh College of Physicians and Surgeons, 2017)
Isolated testicular tuberculosis without renal or pulmonary involvement has not been reported much earlier. The case of a young HIV negative patient with testicular tuberculosis and tuberculoma of brain has been presented. A 32 years old normotensive, non-diabetic farmer presented to emergency facility with sudden onset of severe headache, vertigo and vomiting that developed over 24 hours and mild pain, swelling of right hemiscrotum associated with low grade fever for last one month. On examination, patient was conscious, oriented, pulse rate was 72/min, blood pressure was recorded 130/80 mm Hg, body temperature was 99 degree F, genital examination revealed swelling of right hemiscrotum with enlarged, firm and mildly tender right testis. He refused full neurological examination due to severe Journal of Bangladesh College of Physicians and Surgeons Vol. 34, No. 2, April 2016 headache and vertigo. MRI of brain revealed multiple, hyperintense, ring-enhancing lesions over right cerebellar hemisphere and corpus callosum. Aspiration of scrotal fluid revealed about 50 ml of yellowish pus, microbiology confirmed presence of few acid-fast-bacilli and plenty of pus cells. FNAC from right testicular mass revealed presence of granuloma and caseation necrosis. His chest X-ray and CSF analysis were normal, ESR was 20, USG of abdomen, hepatic and renal work-up was normal. Soon the patient was started with category I antituberculosis drug along with intravenous steroids. An excellent symptomatic improvement developed on 5th day of initiating drug therapy, he was closely monitored and followed up after discharge. This case report was prepared with his full consent. J Bangladesh Coll Phys Surg 2016; 34(2): 112-114